MODUS PERDAGANGAN MANUSIA MELALUI PENYALAHGUNAAN VISA UMROH DALAM IMPLEMENTASI KEBIJAKAN MORATORIUM PEKERJA MIGRAN INDONESIA INFORMAL KE ARAB SAUDI TAHUN 2015 – 2017 - Muhamad Ahsanul Habib Habib; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
For the last 10 years, Saudi Arabia still the third most popular country as a destination for informal Indonesian Migrant Workers candidates. After many reports of violence cases, problems, and threat of death penalty that faced by the migrant workers. The government through the Ministry of Manpower responded the cases through a moratorium policy on the sending and placing of informal Indonesian Migrant Workers in 2011, 2014, and 2015. This study will explain the implementation of moratorium policy implementation as the application of human security values, actually open opportunities for human trafficking through the misuses of umrah visas. This study use qualitative method and the concept of human security to explain how the moratorium policy as a form of Indonesian government’s protection to informal Indonesian Migrant Workers, became a threat for them and Indonesian’s people. The result of this study, shows the application of human security through moratorium policy is only in theoretical studies, but weak in implementations. This study will prove the inconsistency between the consideration and decisions points as a weakness and gaps in the body of the moratorium policy. Then, those weakness will lead to human trafficking cases through the misuses of umrah visas